Cfd simulation of a pilot scale slurry photocatalytic reactor and design of multiple-lamp reactors - Boyjoo, Yashveersingh; Ang, Ming; Pareek, Vishnu (Pergamon, 2014)
The hydrodynamics behaviour and radiation transport occurring inside a pilot-scale slurry photocatalytic reactor (treating real shower water) with large diameter was investigated using computational fluid dynamics (CFD). The multiphase flow system was solved using a granular Eulerian model while the solution of the radiative transport equation (RTE) was solved using the finite volume based discrete ordinate model (DOM). Multiphase simulation showed recirculation zones caused by the high slurry inlet velocity. Due to the rapid attenuation of light occurring radially within the reactor, regions of varying reaction orders exist, i.e., half order reaction close to the lamp and first order reaction further from the lamp, as the incident radiation goes below a certain value. A rate equation relating pollutant degradation to the rate occurring in the half and first order reaction regions (in terms of local volumetric rate of energy absorption – LVREA) was proposed. Using a value of 225 W m-2 as the minimum incident light intensity at which half order reactions take place, a Pearson correlation of 0.88 between simulated and experimental data indicated that the proposed model satisfactorily described the experimental observations. Next, simulations performed with a system of multiple lamps (2 and 4 lamps) at different geometrical arrangements (i.e. with the lamps separated by the distance Xlamp) showed that within the range of catalyst concentration investigated, the maximum potential increases in reaction rate was 56% and 123% when using 2 and 4 lamps (at optimum lamp arrangement) respectively, as compared to using one lamp. The increase in reaction rate occurred due to the maximisation of incident radiation contours at which first order reactions take place. The optimum lamp separation was dependent on the catalyst concentration in the wastewater and decreased with increasing catalyst concentration.